PENGELOLAAN PEMBELAJARAN PROGRAM AKSELERASI DI SDN MANGKUBUMEN KIDUL NO.16 SURAKARTA - SASANTI, IRMA HARI, Prof. Dr. Sutama, M.Pd (2017)
ABSTRACT Irma Hari Sasanti. Q 100090006. The Learning Management of Acceleration Program in SDN Mangkubumen Kidul No. 16 Surakarta. Thesis. Postgraduate Program. Muhammadiyah Surakarta University. 2017. Mentor: Prof.Dr.Sutama, M.Pd. Organizing acceleration Program is very important because by giving the appropriate education service for the students' need with intelligence ability and special talent will give the chances for students in developing their intelligence and talent well, therefore it is hoped that those children will grow being the intelligent, skillful, and have good morals to welcome the bright future of this nation in facing the globalization era.This is so important so a good management system including planning, acting, and evaluating in organizing the acceleration program is really needed.The purposes of this research are for: 1) to know and to describe planning, acting, and evaluating the learning activity of acceleration program in SDN Mangkubumen Kidul No. 16 Surakarta including the curriculum development, supporting facilities and infrastructures, the teacher recruitment and also the student recruitment of acceleration program. 2) to know and to describe the supporting and inhibiting facts of acceleration program in SDN Mangkubumen Kidul No. 16 Surakarta. This research is a qualitative research which uses ethnographic design to understand deeply about acceleration learning program in SDN Mangkubumen Kidul No. 16 Surakarta. The techniques in collecting the data are observing, review, and document analysis. The document analysis through data reduction, presentation of data, and verification. The result shows that the learning management of acceleration program in SDN Mangkubumen Kidul No. 16 Surakarta: 1) The curriculum development has not fully referring to deferential curriculum and has not fully giving attention about the development of interest and talent of students CIBI (Cerdas Istimewa Bakat Istimewa) in SDN Mangkubumen Kidul No. 16 Surakarta. 2) The facilities and infrastructure for acceleration students is quite adequate. 3) The students recruitment is appropriate in accordance with the guidelines in accepting students acceleration program. 4) The learning process of acceleration program is very well where we can find the student activity. 5) Supervision goes pretty well but not in maximum level because supervision has not involved the parents and psychologists. 6) The supporting factor of learning management in SDN Mangkubumen Kidul No. 16 is the support of all school stakeholder such as IOM (Ikatan Orang Tua Murid), while the obstacle factor is the lack of teachers that specially handle students CIBI (Cerdas Istimewa Bakat Istimewa). Suggestions for SDN Mangkubumen Kidul No. 16 in developing the acceleration program are: 1) To reach the optimum achievement especially the management of CIBI school needs to develop effective and differential curriculum. 2) To handle social obstacle and boringness of students it is suggested to the teacher to prepare means of learning especially lesson plan which leads to cooperative learning so the students can do interaction with other students. 3) It should be held special selection and training continually for teachers who will teach in acceleration program so that it will obtain the competent teacher in his field. Key words: learning management, acceleration, special intelligence.